2014
DOI: 10.1308/003588414x13824511649256
|View full text |Cite
|
Sign up to set email alerts
|

Pain after laparoscopic antireflux surgery

Abstract: Pain following laparoscopic antireflux surgery occurs in over 20% of patients. Some have an obvious complication or a diagnosis made through routine investigation. Most have mild to moderate pain with minimal effect on quality of life. In a smaller proportion of patients, pain is severe, persistent and can be disabling. In this group, diagnosis is more difficult but systematic investigation can be rewarding, and can enable appropriate and successful treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Pain was mild or moderate in the majority and severe in 4% of patients. Neither frequency nor severity of pain was associated with operation type [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain was mild or moderate in the majority and severe in 4% of patients. Neither frequency nor severity of pain was associated with operation type [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of rectal pain after laparoscopic "rectal" cancer surgery has been reported at 13.5% and after laparoscopic surgery for endometriosis, chronic PP has been reported by 27%-38% at mid to long-term FU [22][23][24] Additionally, pain after laparoscopic antireflux surgery occurs in over 20% of patients and 8%-16% experience chronic pain to a degree that impairs their daily lives after an inguinal hernia repair. [25][26][27] Our results show 47% of the patients reported improvement in their pre-LVMR PP at long-term FU, however, de-novo PP which lasted for more than 3 months was reported by 15% of the patients. In our view, PP in patients presenting with rectal prolapse may be a complex interplay of mechanics and neurogenic pain, often complicated by the impact of chronic pain syndrome.…”
Section: Discussionmentioning
confidence: 58%
“…The incidence of rectal pain after laparoscopic “rectal” cancer surgery has been reported at 13.5% and after laparoscopic surgery for endometriosis, chronic PP has been reported by 27%–38% at mid to long-term FU 2224 Additionally, pain after laparoscopic anti-reflux surgery occurs in over 20% of patients and 8%–16% experience chronic pain to a degree that impairs their daily lives after an inguinal hernia repair. 2527…”
Section: Discussionmentioning
confidence: 99%
“…Women reporting pain were younger, with associated factors of early postoperative pain, fibromyalgia, worse physical health and somatization [38]. Similarly, Bunting et al [39], in a systematic review, included 17 studies containing 2737 patients who underwent laparoscopic antireflux surgery and observed that over 20% of patients reported pain at a median follow‐up of 43 months.…”
Section: Discussionmentioning
confidence: 99%